2011
DOI: 10.3758/s13414-011-0191-x
|View full text |Cite
|
Sign up to set email alerts
|

Does oculomotor inhibition of return influence fixation probability during scene search?

Abstract: Oculomotor inhibition of return (IOR) is believed to facilitate scene scanning by decreasing the probability that gaze will return to a previously fixated location. This "foraging" hypothesis was tested during scene search and in response to sudden-onset probes at the immediately previous (one-back) fixation location. The latencies of saccades landing within 1º of the previous fixation location were elevated, consistent with oculomotor IOR. However, there was no decrease in the likelihood that the previous loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
57
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 76 publications
(175 reference statements)
11
57
4
Order By: Relevance
“…Furthermore, no such evidence was found in the fine-grained analysis of fixation position focusing on letter position with a fixated word. These results are consistent with recent results from scene viewing and search suggesting that temporal O-IOR need not be accompanied by spatial O-IOR (Hooge et al, 2005;Smith & Henderson, 2009, 2011a. Although reading is a relatively young skill from the perspective of evolution, it appears to draw on much older systems developed for controlling the dynamic allocation of attention and eye movements.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Furthermore, no such evidence was found in the fine-grained analysis of fixation position focusing on letter position with a fixated word. These results are consistent with recent results from scene viewing and search suggesting that temporal O-IOR need not be accompanied by spatial O-IOR (Hooge et al, 2005;Smith & Henderson, 2009, 2011a. Although reading is a relatively young skill from the perspective of evolution, it appears to draw on much older systems developed for controlling the dynamic allocation of attention and eye movements.…”
Section: Discussionsupporting
confidence: 82%
“…In this way, O-IOR could facilitate eye movement control by helping observers avoid reinspecting recently fixated locations (Klein, 1988;Klein & MacInnes, 1999). Evidence concerning this hypothesis is currently mixed, with several reports of equal or greater refixation of previously fixated locations in visual search and scene viewing (Hooge et al, 2005;Smith & Henderson, 2009, 2011a, 2011b. In the present study, little evidence for spatial consequences of O-IOR on fixation probability was observed.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations